Plan de mejoramiento de buenas prácticas de manufactura para ´BPM´ a la manipulación de alimentos en el área de producción para ´Recepciones y Banquetes Las Palmas´ - Gómez Caiza, Joselyn Alejandra (2017)
The food and beverage industry has a trajectory from very remote times where only men or people of high social status met in exclusive dining rooms, over the years these establishments have been developing abysmal. With the development of the industry, quality control systems were created in the case of foods and beverages. Good Manufacturing Practices were promoted, which consists of the safety of the product during the production processes until its delivery to the customer. Receptions and Banquets Las Palmas has offered its service in social events for more than 22 years, they have 10 people working most of them are empirical. The objective of this research is to establish a plan to improve Good Manufacturing Practices, directing the establishment to improve the quality of the final product, based on control processes of raw material handling, from the purchase and verification of Quality until its final delivery to the diner. Finally, the following tools were developed as an implement for the improvement plan: manual of implementation of Good Manufacturing Practices, flow of reception and food handling, with which it is expected to have a favorable result in the standardization and control of the processes Made in Receptions and Banquets Las Palmas, in order to reach the customer with a high quality product.